The effect of curing time on compressive strength of composite cement concrete - Uddin, Md; Jameel, Mohammed; Sobuz, Habibur Rahman; Hasan, Noor Md; Islam, Md; Amanat, Khan Mahmud (2012)
The effect of curing condition of five different composition of Portland composite cement (PCC) and ordinary Portland cement (OPC) were investigated in this study. Compressive strength development of five different concrete types has been investigated in terms of cement content and curing duration. From the experimental observation, it is found that the early age strength of concrete made with PCC is lower than that of concrete made with OPC due to the presence of fly ash in PCC which is responsible for the pozzolanic reaction. The continued pozzolanic activity of fly ash contributes to increase strength gain at later ages at continued curing condition. It is also found that drying ambient conditions reduction of the strength potential of concrete made with PCC because the secondary (pozzolanic) reaction fails to contribute to the development of strength.